Theory and language of climate change communication - Nerlich, Brigitte; Koteyko, Nelya; Brown, Brian (Wiley Publishing, 2010)
Climate change communication has become a salient topic in science and society. It has grown to be something like a booming industry alongside more established ‘communication enterprises’, such as health communication, risk communication, and science communication. This article situates the theory of climate change communication within theoretical developments in the field of science communication. It discusses the importance and difficulties inherent in talking about climate change to different types of publics using various types of communication tools and strategies. It engages with the difficult issue of the relationship between climate change communication and behavior change, and it focuses, in particular, on the role of language (metaphors, words, strategies, frames, and narratives) in conveying climate change issues to stakeholders. In the process, it attempts to provide an overview of emerging theories of climate change communication, theories that recently have begun to proliferate quite dramatically. In some cases, we can, therefore only provide signposts to the most relevant research that is being carried out with regard to climate change communication without being able to engage with all its aspects. We end with an assessment of how communication could be improved in light of the theories and practices discussed in this article.